Evidence of transitioning apple farming to an agro-ecological model in Himachal Pradesh - Divyanshu,; Sharma, Subhash; Chandel, Rajeshwar Singh; Vashishat, Rohit; Verma, Subhash Chander; Verma, Sudhir; Bharat, Narender Kumar; Thakur, Kuldeep Singh; Dev, Inder; Chauhan, Sanjeev; Chandel, Ashu; Kishore, Kamal; et al. (Frontiers in Nutrition, 2025)
Agro-ecological farming practices that integrate economic viability and environmental resilience, based on principles designed to support optimal food and nutritional security in farming systems. This study compares Natural Farming (NF) and Conventional Farming (CF) in apple orchards of Himachal Pradesh by using agro-ecological indicators to assess soil health, pest management, and profitability. The research was conducted across the High Hills Temperate Wet (Zone III) and Dry Temperate High Hills (Zone IV). A total of 140 farm (70 under Natural Farming and 70 under Conventional Farming) were sampled by using simple random sampling method and Structural Equation Modeling (SEM) was used to analyze the interrelationships among soil nutrient status, pest and disease incidence, and farm profitability. The results revealed that NF had higher organic carbon (OC) levels, ranging from 0.84 to 1.95%, compared to CF, which ranged from 0.53 to 1.91%. NF also exhibited higher nitrogen (N), phosphorus (P), and micronutrient levels, while potassium (K) levels were lower. Pest incidence was significantly higher in NF, with Woolly Apple Aphid (50.08%) and Leaf Folder (41%) infestations, compared to CF (17.5 and 5.5%, respectively). NF also showed a 1.59% increase in yield (161.25 quintals/ha) and a 46.76% reduction in total variable costs. Structural equation modeling (SEM) identified key pathways linking farming practices to soil quality, yield performance, and economic outcomes. The analysis revealed that organic matter positively influenced microbial activity (0.05), thereby enhancing soil fertility. SEM findings also highlighted the importance of balanced nutrient management for sustaining both productivity and profitability. These results underscore NF’s capacity to support agro-ecological indicators by enhancing both economic and environmental resilience, while encouraging long-term nutritional security through this agro-ecological supported system. This research provides compelling evidence for adopting NF as a transformative approach in apple farming systems.